L.S. Petruševskaja nello specchio di vita e arte: la «scrittrice con una biografia» - Marcucci, Giulia (L'ospite ingrato, 2023)
The literary work by L. Petruševskaja can be compared to the thick forest full of intertwining branches with which the memoir The Girl from the Metropole begins. Untangling this labyrinth is not easy, due to the variety of genres covered by the author and the hostile work of Soviet censorship, which only allowed the publication of the short stories, plays and fairytales with continuity after Perestroika. The fact that this memoir was written and published in 2006, i.e. long after the 1938-1948 decade, and especially almost forty years after Petrushevskaya’s debut at the turn of the 1960s and 1970s, is only an apparent paradox. Indeed, there is no doubt that the largely traumatic experience of childhood required a lengthy reworking, as well as an appropriate cultural context, before it could be shared with readers. The hypothesis from which this contribution moves is that the memoir, together with other autobiographical novels and essays from the 2000s, can be seen not so much as a ‘landing point’, but rather as a pivot around which a critical reinterpretation of the work of the Russian narrator and playwright develops. Thus, proceeding from autobiographical prose and non-fiction, and back through theatre and fairytales, this contribution offers the Italian reader a partial presentation of Petrushevskaya’s work and poetics in relation to her life and the history of an entire country.